Comparison of glimepiride and linagliptin in the treatment of non-alcoholic hepatic disease with type 2 diabetes mellitus - Feng Tian; Yali Guo; Liping Zhou; Qunying Yao; Xiaoyan Liang; Jiaxin Lu; Aiping He; Jie Shen (Archives of Medical Science)
Introduction Nonalcoholic fatty liver disease (NAFLD) with type 2 diabetes mellitus (T2DM) is associated with severe clinical outcomes. MicroRNA (miR)-210 has been reported to be related to T2DM and lipid metabolism. This study aimed to determine whether miR-210 can predict the effects of glimepiride and linagliptin on NAFLD with T2DM.